Isolasi Dan Uji Aktivitas Bakteri Proteolitik Yang Berasosiasi Dengan Spons Stylotella Sp. Dan Potensinya Sebagai Antibakteri - Seuk, Mariana Septiani; Pardosi, Lukas; Fallo, Gergonius; Manalu, Adelya Irawan (BIOEDUSCIENCE, 2024)
Background: The province of East Nusa Tenggara (NTT), Indonesia, boasts a significant expanse of marine territory, making its waters a potential treasure trove of aquatic resources. One such marine resource is the Stylotella SP sponge, which is found in this region. Sponges like Stylotella SP often have intricate relationships with microorganisms, including bacteria. Method: This research was to characterize and identify proteolytic bacteria and test bioactive compounds from isolates of proteolytic bacteria from the sponge Stylotella sp. Proteolytic bacterial strains were rejuvenated first in 2% TSA + Nacl medium and then characterized microscopically and biochemically using catalase and oxidase tests. The diffusion method used the antibacterial activity test against E.coli and S. aureus. Result: The results showed that proteolytic bacterial isolates had irregular and rounded colony shapes, wavy and intact colony edges, hilly and convex colony elevation, and white color, while biochemically, it was declared positive for the catalase and oxidase tests. Antibacterial activity tests on proteolytic bacterial strains showed the ability to inhibit the growth of Staphylococcus aureus with an inhibitory capacity of 9.5 mm and Escherichia coli with an inhibitory capacity of 7 mm.